PROBABILISTIC FORECAST SYSTEM OF RAINFALL EVENT IN BANDUNG REGION USING MODEL OUTPUT STATISTIC SCHEME - Noer Hadi (NIM : 12814023), Anugrah
Statistical Guidance developed on this research using WRF model prediction outputs by Weather and Climate Prediction Laboratory of Institute Technology of Bandung (WCPL ITB). Model Output Statistic (MOS) scheme used on Statistical Guidance approach to forecast probability of rainfall event on January Ã‚Â– March period in Bandung Region. Forecast times divided into three times; forecast day 1, forecast day 2, and forecast day 3 to forecast probability of rain event for three days. To increase the accuration, optimal point approximation is applied. The result verified using Brier Score and compared with time-lagged ensemble scheme using Brier Skill Score. This research shows that optimal point lies in Southwestern Bandung, around Ciwiday and Rancabali. The combination between optimal point and local point can increase the accuration approximately 0.2 up to 0.3. The comparison result between MOS scheme and time-lagged scheme shows that MOS more accurate 20% up to 70% on rainfall event forecasting.